INFLUENCE SUPPORT COLLEAGUE WORK , LEADERSHIP STYLE AND COMMUNICATION TO MPM MOTOR PONOROGO DEALER PRODUCTIVITY - Mustopa , Arga Saiful; Hartono , Sri; Kristiyana , Naning (Proceeding of International Conference on Social Science and Humanity, 2024)
General Background: Productivity is a crucial indicator of a company's success, driven significantly by human resources, especially during challenging times. Specific Background: Effective management of human resources, including fostering a conducive work environment, leadership style, and communication, is essential to optimize employee performance and achieve organizational goals. Knowledge Gap: While the impact of peer support, leadership style, and communication on employee productivity is acknowledged, specific evidence within the context of motor dealerships, particularly in Indonesia, remains underexplored. Aims: This study investigates the influence of peer support, leadership style, and communication on employee productivity at the Honda MPM Motor Ponorogo Dealer. Results: The study, conducted using a quantitative approach with data collected from 50 employees through questionnaires, revealed that peer support, leadership style, and communication each significantly and positively impact productivity. The results were validated through multiple linear regression analysis using SPSS. Novelty: This research highlights the simultaneous and significant effects of these factors on productivity within a motor dealership context, providing specific insights into the Indonesian market. Implications: The findings suggest that enhancing peer relationships, adopting effective leadership practices, and improving communication can substantially boost employee productivity. For the MPM Motor Ponorogo Dealer, these results offer actionable recommendations, such as fostering better interpersonal understanding among employees, encouraging leadership to motivate and guide, and providing communication training. Future research is encouraged to explore additional factors influencing productivity, such as work motivation and competency, to build on these findings